Enhancement of the Production of Tropane Alkaloids in the Hyoscyamus Niger L. Callus Using Different Biotic Elicitors - Abed, Ashwaq S.; Jassim, Emad Hamdi (Iraqi Journal of Science, 2024)
This study looked at the amount of tropane alkaloids in both the leaves of the mother plant and the callus cultures of Hyoscyamus niger L. It also looked at how biotic elicitation affects the growth of callus cultures and increases the production of alkaloids. The investigation identified and quantified three primary tropane alkaloids (Hyoscyamine, Scopolamine, and Atropine) from both sources. Remarkably, the callus cultures exhibited obviously higher levels of alkaloids in comparison to the leaves of the mother plant, implying their potential as a valuable reservoir for alkaloid production. Concerning the effects of biotic elicitation, the study showed that the application of chitosan (CHT), yeast extract (YE), and fungal extract of Trichoderma asperellum yielded a substantial decrease in callus weight when contrasted with the control group. This decrease became more pronounced with escalating concentrations of the elicitors. In terms of alkaloid synthesis, a clear correlation between the concentration of bio stimulants and tropane alkaloid levels was established. Particularly, CHT elicitation displayed the most pronounced enhancement in levels of tropane alkaloids among the three elicitors. Notably, the highest CHT concentration of 40 mg/L yielded the most elevated levels of alkaloids, measuring at 25.3 µg/g for Hyoscyamine, 31.2 µg/g for Scopolamine, and 21.5 µg/g for Atropine. This represents approximate percentage increases in concentration of 208%, 183%, and 198%, respectively, when compared to the control treatment. Generally, these findings carry significant implications for advancing tropane alkaloid biosynthesis, with potential applications spanning the pharmaceutical and biotechnology sectors.